Power as knowledge. The reverse logic of the post-scientific world - Kobylarek, Aleksander (Journal of Education Culture and Society, 2020)
This article deals with the causes and effects of a surrender to anti-science in social development. Populist governments support the idea of anti-science in an attempt to win over poorly-educated electors. The text analyses the fundamental characteristics of the pressure mechanisms adopted by populist movements, and points to the system of measures in various spheres which help in fostering general ignorance and support anti-scientific operations. For the agents of power science, and the system of values which accompanies it, becomes a target to attack. Simultaneously, for the average person scientific knowledge ceases to be the basis of analysis and interpretation of different phenomena. Anti-science regimes support anti-science movements in order to manipulate society and disrupt potential opposition. This is possible thanks to superficial education and not enough emphasis on critical thinking within the education system, because less discerning citizens will go along with an anti-science regime.            Analysis leads to the conclusion that the narrow short-term material interest of the regime is its only value, to which all others are subordinated, including Plato’s triad. In the face of a lack of understanding on the part of the authorities, education based on episteme is not possible, at least not entirely. This article suggests the need for change in the philosophy of education to one where the major emphasis is on quality and prioritised content.